Pemanfaatan Berbagai Jenis Limbah Pertanian Sebagai Media Tanam Jamur - Fery Kurniawan (Bioedunis Journal, 2022)
Mushrooms are divided into two major groups, namely white rot fungi and brown rot fungi. White rot mushrooms are a group of fungi that easily grow on medium containing cellulose/simple sugars such as bagasse and grass residue, while brown rot mushrooms are a group of fungi that grow easily or well on medium containing complex cellulose such as residue from dead wood. Mushrooms are classified as heterotrophic living things, which means they live by processing food from organic compounds. In general, the substrate used for growing mushrooms is sawdust, but the problem found is the availability of sawdust which is difficult to obtain and costs a lot of money to procure. An alternative substrate that is easy to obtain and widely available is agricultural waste. The purpose of this research is to observe and examine from various sources what types of waste can be used as an alternative for cultivating mushrooms so as to save on production costs. This type of research is applied science research with the method used is the survey study method of literature. The results obtained are the types of waste that can be used as a mushroom growing medium are Sawdust, Coconut Fiber, Oil Palm Empty Bunches, Oil Palm Male Flowers, Palm Oil Stem Decomposite, Rice Husk, Rice Bran, Corn Cobs, Leftover Corn Seeds, Leftover Sorghum Seeds, Remaining Wheat Seeds, Sugar Cane Dregs, Dried Tea Powder, Dried Coffee Skins, Dried Peanut Shells. It is suggested that further research is needed on mixing the composition of mushroom growing media so that maximum results are obtained for the growth of both brown rot and white rot mushrooms